Development of “Pop-Up Book for Kids” as a Learning Media Science theme “Perubahan Cuaca” for Student of Class 3 Elementary School - Johara Aulia Zaeni; Eny Winaryati; Eko Yuliyanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This study aims to develop “Pop-Up Book for Kids” as a learning media science worthy of use of theme “Perubahan Cuaca” for student of 3rd grade primary school. The model of this research is the development of Borg and Gall procedural methods.   Data were obtained from two specialist material lecturers, two specialist media, two elementary school science teacher as reviewer and students as respondents. In this study, there were three and  five students of class 3  in  limited test  from SD Negeri Kedungmundu. Techniques of data collection were observation, questionnaires, and interviews. the results of the above tests can be concluded that the Pop-Up Book for Kids media can attract students interest in the learning process, this is based on the results of observations that have been done. Based on the results of interviews with one of the subjects of research, according to him learning with this media is very fun because many colors and interesting with the existence of some Pop-Up Book techniques that appear this way studentthinks easier in understanding the material.